Design of remote temperature monitoring system on automatic filling R125 Shinva machine using LM35 sensor and Arduino Uno microcontroller - Atmaji, Fransiskus Tatas Dwi (International Journal of Integrated Engineering, 2020)
This paper proposed the design of a remote temperature monitoring system of R125 Shinva’s automatic filling machine. The R125 Shinvaâ€™s automatic filling machine is one of the machines on SF company which main function is fulfilling the infusion liquid into the infusion packaging, this infusion liquid is mainly used for the human medical treatment. Based on the failure history data, this machine has the highest downtime among the others and one of the fatal failures is caused by the overheating of the heating element in the infusion liquid bag’s transfer system. Using the proposed design, the temperature of the heating element can be monitored in real-time condition and also giving notification to the maintenance team for the next maintenance action. With the power of cloud-based technology, the monitoring system not only on-site monitoring but also can use a web server monitoring, and mobile monitoring system.